THE ROLE OF INTERPRETERS AND COURT INTERPRETING - NARTOWSKA, Karolina (Comparative Legilinguistics, 2013)
Court interpreters play a central and crucial role in multilingual communication between participants to the proceedings in the court room. The author points out that the interpreter is still frequently considered as a machine automatically converting a message in one language into another. The paper is devoted to the reality of court interpreting and strategies adopted by interpreters to provide successful court communication. The reasearch has been carred out in Austrian courts. It revealed that interpreters are not only intermediaries in cross-lingual and cross-cultural communication but also they often must co-ordinate court interactions. It is concluded that interpreters are active participants in court proceedings and experts in transcultural communication.